Classification of Systemic Lupus Erythematosus: Systemic Lupus International Collaborating Clinics Versus American College of Rheumatology Criteria. A Comparative Study of 2, 055 Patients From a Real‐Life, International Systemic Lupus Erythematosus Cohort. Issue 8 (August 2015) - Inês, Luís; Silva, Cândida; Galindo, Maria; López‐Longo, Francisco J.; Terroso, Georgina; Romão, Vasco C.; Rúa‐Figueroa, Iñigo; Santos, Maria J.; Pego‐Reigosa, José M.; Nero, Patrícia; Cerqueira, Marcos; Duarte, Cátia; et al.
<x xml:space="preserve">Abstract</x> Objective The new Systemic Lupus International Collaborating Clinics (SLICC) 2012 classification criteria aimed to improve the performance of systemic lupus erythematosus (SLE) classification over the American College of Rheumatology (ACR) 1997 criteria. However, the SLICC 2012 criteria need further external validation. Our objective was to compare the sensitivity for SLE classification between the ACR 1997 and the SLICC 2012 criteria sets in a real‐life, multicenter, international SLE population. Methods We conducted a cross‐sectional observational study of patients with a clinical diagnosis of SLE followed at the participating rheumatology centers and registered in the Portuguese and Spanish national registries. The sensitivity of the 2 classification sets was compared using McNemar's test. The sensitivity of ACR 1997 and SLICC 2012 was further examined in 5 subgroups, defined according to disease duration. Results We included 2, 055 SLE patients (female 91.4%, white 93.5%, mean ± SD age at disease onset 33.1 ± 14.4 years, mean ± SD age at SLE diagnosis 35.3 ± 14.7 years, and mean ± SD age at the time of the study 47.4 ± 14.6 years) from 17 centers. The sensitivity for SLE classification was higher with the SLICC 2012 than with the ACR 1997 (93.2% versus 85.6%; P < 0.0001). Of 296 patients not fulfilling the ACR 1997, 62.8% could be classified with the SLICC 2012. The subgroup of patients with ≤5 years since disease onset presented the largest difference in sensitivity between the SLICC 2012 and the ACR 1997 (89.3% versus 76.0%; P < 0.0001); this difference diminished with longer disease duration, and it was no longer significant for patients with >20 years of disease duration. Conclusion The SLICC 2012 criteria were more sensitive than the ACR 1997 criteria in real‐life clinical practice in SLE. The SLICC 2012 criteria may allow patients to be classified as having SLE earlier in the disease course.